Biochemical and molecular aspects of spectral diagnosis in calcinosis cutis. (11th March 2014) - Lin, Shan-Yang
Abstract : Calcinosis cutis (CC) is a type of calcinosis wherein insoluble compounds or salts deposited on the skin. Clinical diagnosis of CC is usually achieved through time consuming histopathological or immunohistochemical procedures, but it can only be empirically identified by experienced practitioners. The use of advanced vibrational spectroscopy has been recently shown to have great potential as a diagnostic technique for various diseased tissues because it analyses the chemical composition of diseased tissue rather than its anatomy and predicts disease progression. This review article includes a summary of the application of Fourier transform infrared (FT-IR) and Raman spectroscopic or microspectroscopic analysis for the rapid diagnosis and identification of the chemical composition of skin calcified deposits in patients with various CC symptoms. Both advanced techniques not only can detect the types of insoluble salts such as calcium phosphate, calcium carbonate, and monosodium urate, and β-carotene in the calcified deposits of human skin tissue but also can directly differentiate the carbonate substitution in the apatite structure of the skin calcified deposits. In particular, the combination of both vibrational techniques may provide complementary information to simultaneously assess the intact components of the calcified deposits. In the future, both FT-IR and Raman vibrational microspectroscopic techniques will become available tools to support the standard test techniques currently used in some clinical diagnoses. Molecular spectroscopy technique is rapidly changing disease diagnosis and management.